COVID-19 and the Libraries : What is left for Private Copying Exception? - A Greek Copyright Law approach - Chiou, Theodoros (Journal of Integrated Information Management, 2024)
The present paper deals with copying, which is a tool that renders users’ access in library’s physical material more efficient as it allows users to repeatedly access, i.e., study the copied material portably, without the need of repeated physical presence within opening hours of libraries’ premises and without reserving the physical medium during their presence. However, during the COVID-19 pandemic, what is left for private copying except for the library’s physical material, when the only available alternative for users is distant or no access to the library’s collection? This paper questions whether Greek Copyright Law in force would accommodate the realization of “distant private copying” of library’s physical material by users, especially in view of the fact that in situ access of users has been prohibited or suspended by law.